PENENTUAN DAN PENGUNGKAPAN PENDAPATAN DAN BEBAN MENGGUNAKAN METODE PENENTUAN TAHAP PENYELESAIAN SUATU KONTRAK DAN WAKTU PENGAKUAN PENDAPATAN DAN BEBAN KONTRAK - Muda, Markus; Naa, Khofifah; Apa, Fiu La (LPPM Politeknik Saint Paul Sorong, 2019)
Revenue should be measured by the fair value of earned or earned rewards. The amount of revenue arising from a transaction is usually determined by an agreement between the company and the buyer or user of the actuva. AIA (IASC) defines costs in Financial Accounting Standards (2002) as follows: Expense is a decrease in economic benefits during an accounting period in the form of outflows or reduced assets or the occurrence of liabilities that result in a decrease in revenue that does not involve distribution to investors. According to AIA (2010) in the percentage settlement method, contract revenue is related to contract costs incurred in reaching the completion stage. Fair value as the price that will be accepted to sell the asset or the price that will be paid to transfer a liability in an orderly transaction between market participants on the measurement date. During the early stages of a contract, it often happens that the outcome of the contract cannot be estimated reliably. However, it is possible that the entity will recover the contract costs incurred